Pengaruh Bauran Pemasaran Terhadap Keputusan Anggota Menggunakan Produk Pembiayaan Musyarakah Pada BMT UGT Sidogiri Capem Seruni Kota Pontianak - Endika Pratama (Universitas Muhammadiyah Pontianak, 2014)
This study examines the effect of the marketing mix to the decision to use members of Musharaka financing products at BMT UGT Sidogiri Capem Seruni Pontianak. This type of research is descriptive method, data collection techniques used were questionnaires, interviews, observation, and documentation. The study population was all the members who use the product Musharaka financing. The sample of 100 respondents drawn through a non-probability sampling technique, with a sample size of 100 people. The analysis tool is Regression Simple Linear, Correlation, Determination and Test F. Regression analysis yields the equation Y = 1.399 + 0,605X. From the results of correlation (R) obtained at 0.421. This value can be interpreted that the influence of marketing mix to decision of selectingmembers Musharaka financing products at BMT UGT Sidogiri Capem Seruni Kota Pontianak is a strong positive. The value of the coefficient of determination (KD) obtained was 0.178%. From these test results that the marketing mix is significantly have influence on the consumer decisions, and these test results that the marketing mix is significantly have influence on the decision of members. Test regression modelscalculated F value of 21.159 with a significance value (sig) of 0.000, meaning that the value of significance (sig) is much smaller than 0.05.